A Fatal Case of COVID-19 in an Infant with Severe Acute Malnutrition Admitted to a Paediatric Ward in Niger - Alido Soumana; Aboubacar Samaila; Lamine Mahaman Moustapha; Moumouni Kamaye; Balkissa Daouda; Ibrahim Alkassoum Salifou; Adamou Lagare; Eric Omar Adehossi; Maman Laminou Ibrahim (Case Reports in Pediatrics)
While there have been very few fatal cases, SARS-CoV-2 has been reported in paediatric patients. This study aims to describe a fatal case of COVID-19 in a child with severe acute malnutrition. The eight-month-old child presented with fever, diarrhoea, and difficulty in breathing. The mother of the child had fever and shortness of breath four weeks before she died. Physical examination revealed lethargy, dehydration, and severe weight loss with a weight of 5 kg at a height of 78 cm tall. The weight-for-height index was less than three Z-scores, which corresponds to severe acute malnutrition. The pulmonary examination revealed moderate respiratory distress, and the chest X-ray presented features suggestive of pneumonia in the right lung area. In the context of the COVID-19 outbreak in Niger and the circumstances of the mother’s death, a nasal swab was taken for laboratory confirmation. Treatment provided to the child included intranasal oxygen, antibiotics, and a dietary program with therapeutic milk. The child died 48 hours after his admission. The history of contact with a SARS-CoV-2 suspect or positive patient should lead to screening for infection by using RT-PCR. It is important to investigate malnutrition as a potential risk factor for severe SARS-CoV-2 infection and resultant mortality.